EVALUATION OF THE NOTIFICATION PROFILE OF ADVERSE EVENTS RELATED TO CHLOROQUINE AND AZITHROMYCIN BEFORE AND DURING THE COVID-19 PANDEMIC - Alencar, Thalyta dos Santos; Araújo, Amanda Fernandes Borges de; Freitas, Aline de Araújo; Pinto, Emerith Mayra Hungria (CIPEEX, 2025)
This study evaluated the profile of adverse event notifications related to the use of Chloroquine and Azithromycin before and during the COVID-19 pandemic. The pandemic led to massive prescribing of these drugs, even without solid scientific evidence proving their efficacy against SARS-CoV-2. Using data from the VigiMed system, adverse event notifications were analyzed for the periods from January 2018 to December 2019 (pre-pandemic) and from March 2020 to December 2021 (pandemic). The results showed a significant increase in notifications during the pandemic, highlighting the severity of adverse effects associated with the indiscriminate use of these drugs. This study emphasizes the importance of evidence-based medical practices and rigorous pharmacovigilance to avoid unnecessary risks to public health. The conclusions reinforce the need for public policies focused on health education and the prevention of self-medication, especially in scenarios of health crises.